A cross-sectional study of the knowledge, skills, and 6 rights on medication administration by nurses at emergency department - Linda Wieke Noviyanti; Andri Junianto; Ahsan Ahsan (PAGEPress Publications, 2023)
Introduction: Medication errors occur when a patient is given the wrong drug or receives incorrect pharmacological therapy. Incorrect drug administration can cause fatal errors resulting in the patient's death. Approximately 44,000-98,000 patients die each year due to medication errors and this condition is found often in the Emergency Room (ER) due to the complexity. Therefore, this study aims to analyze the relationship between nurses' knowledge, skills, and 6 rights on medication at Emergency Department. Design and Methods: This is an analytical observational study involving 70 nurses randomly selected using consecutive sampling and working at the ER department of Saiful Anwar Hospital Malang. Data were collected through a questionnaire and analyzed descriptively to determine the knowledge and skills of nurses and the implementation of the correct principles of medication administration. Results: The results showed that most of the emergency room nurses had good knowledge and skills in applying the correct principles of medicine. However, the majority could not calculate the drug dose accurately. The spearman rank results showed that there was a relationship between knowledge and the 6 correct drug principles (p<0.001, α= 0,05; r = 0.491) with a percentage of 44%. This indicates that a higher knowledge results in the correct implementation of the drug. Similarly, there was a significant positive correlation between skills and proper medicine (p<0.001, α= 0,05; r = 0.378). Conclusions: It can be inferred that a higher nurse's knowledge and skill results in a better administration of medicine.